Iron-Catalyzed S-Arylation of Benzothiazole with Aryl Iodides under Aqueous Medium: Facile Synthesis of Aryl(2-aminoaryl) Sulfides - Lee, Hang Wai; Yung, Ka Fu; Kwong, Fuk Yee (Synlett, 2014)
A simple route for facile access of aryl(2-aminoaryl) sulfide was reported. With the aid of iron(III) chloride catalyst and diamine ligand, benzothiazole was efficiently S-arylated with various aryl iodides (19 examples) in water under air atmosphere. This operationally simple protocol provides aryl(2-aminoaryl) sulfides in moderate to good yields.
Keywords: S-arylation; iron; catalysis; benzothiazole; water